DIGITAL-BASED PAI LEARNING INNOVATION TO INCREASE STUDENT ENGAGEMENT IN THE INDUSTRIAL REVOLUTION 4.0 ERA" - Sintiya, Sindy (Journal of Quality Islamic Education Research, 2025)
The Industrial Revolution 4.0 era brings significant changes in various fields, especially in the education sector. Islamic Religious Education (PAI) as an important part of character and spiritual formation of students must transform to follow technological developments in order to remain relevant and effective. This study aims to examine innovations in digital-based PAI learning that can increase student involvement in the learning process. The approach used is a literature study with a descriptive analytical method to identify and evaluate various technologies and digital learning models applied in the context of PAI. The findings show that the use of e-learning platforms, mobile applications, interactive multimedia, and gamificationsignificantly increases student motivation, active participation, and understanding of PAI materials. This innovation also provides learning flexibility that is in accordance with the characteristics of millennial and Z generation students who are very familiar with digital technology.Therefore, the integration of digital technology in PAI learning is not only a necessity, but also a crucial strategy to produce a faithful generation that is adaptive to changing times.